Cross-validation of the Canadian Assessment of Physical Literacy second edition (CAPL-2) for Spanish children - Mendoza Muñoz, María.; López Gil, José Francisco.; Pastor Cisneros, Raquel.; Castillo Paredes, Antonio Jonathan.; Urbano Mairena, Javier.; Tremblay, Mark; Carlos Vivas, Jorge. (BMJ Publishing Group, 2024)
Background/objective This study aimed to explore physical literacy (PL) using the Canadian Assessment of Physical Literacy, second edition (CAPL-2), adapt it to the Spanish context and provide evidence of its validity for use in Spanish children aged 8-12. Methods A total of 280 students (150 girls, mean age 10.5±0.9 years) from Extremadura (Spain) completed the CAPL-2. Means and SDs were used to present CAPL-2 scores according to age and sex, as well as frequencies to place participants at different PL levels. Confirmatory factor analysis (CFA) was conducted to establish the best model fit for the data. Results The median PL of Spanish children was progressing, and girls had a lower PL than boys for all ages except 12 years. The results supported a four-domain model for the CAPL-2 Spanish version and reported good fit indices after CFA (χ 2 per df ratio=1.118; P (χ 2)=0.256; root mean square error of approximation=0.021; comparative fit index=0.987; Tuker-Lewis index=0.991; normed fit index=0.895). Conclusion The CAPL-2 model is a valid and reliable instrument for Spanish children aged 8-12. It represents the first tool that assesses PL in Spanish children, covering the domains of motivation and confidence, physical competence, knowledge and understanding, and daily behaviour. It may be relevant for all professionals related to physical activity, education and the health field.
Keywords: Young; Niños; Educación; Ejercicio físico; Validación